Object's shadow removal with removal validation - Syed Abu Bakar, Syed Abdul Rahman; Sheikh, U. U.; As'ari, M. A. (Institute of Electrical and Electronics Engineering (IEEE), 2007)
We introduce in this paper, a shadow detection and removal method for moving objects especially for humans and vehicles. An effective method is presented for detecting and removing shadows from foreground figures. We assume that the foreground figures have been extracted from the input image by some background subtraction method. A figure may contain only one moving object with or without shadow. The homogeneity property of shadows is explored in a novel way for shadow detection and image division technique is used. The process is followed by filtering, removal, boundary removal and removal validation.